The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1159/000065723
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Vascular Endothelial Growth Factor in Hemorrhagic Pleural Effusion of Cancer

Abstract: Angiogenic cytokines, such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and angiogenin, are candidates for the induction of pleural effusions because they have been implicated in the induction of neovascularization, vascular permeability, and hemorrhage both in the inflammatory process and in tumor progression. Thus, we hypothesized that these angiogenic factors in effusion might be involved in the clinical manifestation of malignant pleural disease. We measured the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 14 publications
3
40
0
1
Order By: Relevance
“…In addition a VEGF blockade has been identified to lead to marked reductions in ascites formation (1,5,8,19). Cancer-associated effusions contain significantly more VEGF than those resulting from inflammatory diseases, which suggests that VEGF levels are an independent and statistically significant prognostic indicator of survival (20,21). The results of a previous study revealed that hemorrhagic malignant effusions (RBC count, >1x10 4 /µl) exhibit significantly higher VEGF levels (1,942 pg/ml) compared with non-hemorrhagic effusions (202 pg/ml) (P= 0.016) in malignant patients (21).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition a VEGF blockade has been identified to lead to marked reductions in ascites formation (1,5,8,19). Cancer-associated effusions contain significantly more VEGF than those resulting from inflammatory diseases, which suggests that VEGF levels are an independent and statistically significant prognostic indicator of survival (20,21). The results of a previous study revealed that hemorrhagic malignant effusions (RBC count, >1x10 4 /µl) exhibit significantly higher VEGF levels (1,942 pg/ml) compared with non-hemorrhagic effusions (202 pg/ml) (P= 0.016) in malignant patients (21).…”
Section: Discussionmentioning
confidence: 95%
“…VEGF has an important role in increasing vascular permeability during malignant ascites formation (1)(2)(3)(4)(5). Previous studies have revealed that high concentrations of VEGF are detected in the hydrothorax and ascites fluid of cancer patients (20)(21)(22). The vascular permeabilizing activity of VEGF has been reported to be 50,000 times more potent than histamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, VEGF is a multifunctional cytokine with critical roles in vasculogenesis and in both pathological and physiological angiogenesis and lymphangiogenesis [19]. Excluding malignancy, some other pathological conditions, such as hypoxia, pulmonary embolism, hemorrhagic effusions and empyema, could also lead to or present with heightened levels of VEGF [15,16,20]. VEGF also has a central role in wound healing and inflammation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is regulated by a number of angiogenic and antiangiogenic cytokines.Vascular endothelial growth factor (VEGF) is an important mediator of angiogenesis and vascular permeability.It stimulates capillary formation and has specific mitogenic and chemotactic effects on vascular endothelial cells (Zebrowski et al, 1999). VEGF contributes to the formation of MPE because of their involvement in the induction of neovascularization, in vascular permeability, and in hemorrhage (Ishimoto et al, 2002). Endostatin is one of the better-characterised endogenously produced angiogenesis inhibitors, it can activate tyrosine kinase and induce endothelial cells to form various signaling complexes, thereby inducing tumor vascular endothelial cell into the process of apoptosis and inhibiting microvascular generation (O'Reilly et al, 1997;Skovseth et al, 2005).…”
Section: Introductionmentioning
confidence: 99%